Thermo-mechanical analysis of a radiative annular fin - Mallick, Ashis (2018)
The thermo-mechanical reliability is a critical issue in a radiative fin. The radiative dissipation pertaining to enhance heat rejection from the fin surfaces. Due to the temperature gradient, the non-uniform thermal deformation occurs in the fin material. Thermal deformation may cause various defects such as crack propagation, creep, delamination, fatigue failure, erosion and warping. In this study, an analytical model for thermal stresses in an annular radiative fin is presented. The non-linear heat transfer equation with variable thermal parameters has been solved using the homotopy perturbation method (HPM). The comprehensive closed form solution for thermal stresses are obtained from the HPM based temperature field coupled with the classical theory of elasticity. The effects of radiation on the temperature field and thermal stress field are investigated. In addition to forward solution, an inverse analysis has been carried out for estimating the thermal parameters for a reference stress field.